An Analysis of Code Mixing in Bayu Skak’s Videos - Raudatul Hasanah (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2020)
This study investigated the types and factors that influence code mixing in Bayu Skak’s videos. The data in this study are in the form of utterances that contain code mixing in Bayu Skak’s videos. This research was conducted by analyzing the data qualitatively. The research instruments are the researcher herself. There were three videos that was used in this research. The techniques of data collection were done by watching Bayu Skak’s videos one by one, noting down the utterances that contained code mixing, and giving numbers and codes in every utterance that contained code mixing and analysing the data based on Spradley’s theory (1965). The steps of data analysis are domain analysis, taxonomy analysis, componential analysis, and cultural values. The finding of the research described types and factors that influence the code mixing and the total data showed thirty two data used code mixing from types of code mixing which attained eleven data from insertion, eight data of alternation, and eleven data of congruent lexicalization. Then, factors that influence code mixing cover four need for synonymy, four data of social value, three data of intrduction and development of new culture, five data of low frequency or word, five data of oversight, five data of pernicious homonymy, four data of in sufficiently differentiated, and two data of end.